Current knowledge on spinal meningiomas: a systematic review protocol - Erik Edström; Adrian Elmi-Terander; Gustav Burström; Victor Gabriel El-Hajj; Jenny Pettersson Segerlind (BMJ Open)
Introduction Meningiomas are primary central nervous system tumours that arise from both cranial and spinal meninges. Spinal meningiomas occur less frequently than their cranial counterparts and are consequently given less attention in the literature. Therefore, systematic studies are needed to summarise the current knowledge on spinal meningiomas, providing a solid evidence base for treatment strategies. This systematic review of the literature will therefore assess studies describing spinal meningiomas, their epidemiology, diagnostics, treatment and outcomes.Methods and analysis Electronic databases, including PubMed, Web of Science and Embase, will be searched using the keywords “spinal” and “meningioma”. The search will be set to provide only English studies published after 2000 to avoid any conflicts regarding terminology and classification, as well as to reflect the current status. Case reports, editorials, letters and reviews will also be excluded. Reference lists of relevant records will also be searched. Identified studies will be screened for inclusion, by one reviewer in a first step and then three in the next step to decrease the risk of bias. The results will be categorised to allow for a structured summary of the outcomes and their evidence grade conforming to the Grading of Recommendations, Assessment, Development and Evaluation approach. Categories may include: epidemiology, histopathology, radiological diagnostics, surgery, complications, non-surgical or adjuvant treatments, disease outcomes and predictors, and lastly recurrence. This review will summarise the current knowledge on spinal meningiomas to allow for a better understanding of the disease and contribute to improve its management. For clinicians, the systematic collection and grading of available evidence may aid in decision making and for those seeking to further the scientific field, this review may help to identify areas where knowledge is currently lacking.Ethics and dissemination Ethics approval was not required for our systematic review as it is based on existing publications. The results will be disseminated via submission for publication in a peer-reviewed journal.